Intratumoral multinucleated giant cells are not a prognostic pathologic feature in cutaneous melanoma. (30th June 2016) - Srisuttiyakorn, Chutika; Bulloch, Kaleigh; Rodic, Nemanja; Bosenberg, Marcus; Ariyan, Stephen; Narayan, Deepak; Gould Rothberg, Bonnie E.; Galan, Anjela
Abstract : Background: Histopathologic diagnostic features such as tumor thickness, ulceration, mitoses, microsatellitosis and nodal metastases are principal pathologic staging components of cutaneous melanomas. We chose to focus on evaluating the presence of multinucleated giant cells in microscopic sections as a putative novel prognosticating diagnostic feature of melanoma. Methods: We assembled a retrospective cohort comprised of 562 cases of melanoma. We annotated each case for a multitude of known clinicopathologic variables to allow robust statistical evaluation of our cohort. Results: Only 37 cases (6.6%) exhibited the multinucleated giant cells phenotype. Virtually all multinucleated giant cells were localized in the reticular dermis. Of interest, melanomas with multinucleated giant cells were roughly twice more likely to occur on head and neck sites (p = 0.04). Melanomas with multinucleated giant cells phenotype had both comparable melanoma recurrence (p = 0.12) and similar melanoma‐specific mortality when compared with melanomas without multinucleated giant cells phenotype (p = 0.26). Conclusion: Despite prior anecdotal reports possibly linking multinucleated giant cells phenotype to more aggressive clinical course, we find that melanomas with multinucleated giant cells phenotype is not associated with shorter survival.